Cardiovascular Diseases – A Cause to Worry in Indonesia - Suyanto Suyanto; Normalina Sandora; Laode Burhanuddin; Miftah Azrin (STIKes Hang Tuah Pekanbaru, 2011)
Cardiovascular diseases (CVDs), caused by disorders of the heart and blood vessels, have been associated with changes in peoples’ lifestyles due to the improving economy. In Indonesia, the prevalence CVDs tend to increase recently following the improving of national economic development. In controlling CVD, Indonesian Government particularly Ministry of Health have launched CVD control programme including primary, secondary, and tertiary prevention. However, this policy should be disseminated to people. Thus, the general public is more health conscious